A Cross-sectional Study on Coping Strategies in Alcohol Use Disorder Caregiving: Role of Psychoeducational Interventions - Hunny Kalra; Suninder Tung (Journal of Psychiatry Spectrum, 2025)
Background: Family caregivers play a crucial role in managing the complexities of alcohol use disorder (AUD), and the coping strategies they use significantly influence both their well-being and the quality of care provided to the patients. Aim: The present study aimed to explore the role of psychoeducational interventions (PEIs) on the coping strategies of caregivers of individuals with AUD. Materials and Methods: A total of 128 caregivers were included in this comparative, cross-sectional study, with 38 caregivers in the intervention group who regularly attended PEI sessions for at least 1 year and 90 caregivers in the control group who had never attended, allowing for a between-group comparison of coping strategies. The sessions covered the biopsychosocial causes of AUD, taught coping strategies tailored to caregivers’ needs, provided problem-solving skills, and offered a platform for catharsis. The assessment tool utilized was Brief-COPE (Carver, 1997). Statistical Analysis: Descriptive statistics, independent sample t-test, and effect size analyses were used. Results: Caregivers attending psychoeducational classes demonstrated significantly higher scores in adaptive coping strategies (M = 50.74, standard deviation [SD] = 5.525) compared to nonparticipants (M = 46.76, SD = 6.051). Similarly, maladaptive coping strategies were significantly lower in the intervention group (M = 18.08, SD = 4.226) than in the nonparticipating group (M = 22.19, SD = 5.396). These findings, with medium to large effect sizes, underline the substantial practical benefits of PEIs. Conclusion: The findings suggest the need to integrate PEIs into standard care protocols for AUD patient support systems. Future research should include randomized controlled trials to establish a cause-and-effect relationship between PEIs and coping strategies employed by AUD caregivers.